ANALISIS RASIO KEUANGAN DALAM PENILAIAAN KINERJA KEUANGAN PEMERINTAH DAERAH (Studi Kasus pada Pemerintah Daerah Kabupaten Rokan Hilir Tahun Anggaran 2011-2016) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the analysis of financial performance in termsof regional independence ratios, regional income efficiency ratios, regionalincome effectiveness ratios, regional expenditure efficiency ratios and economicratios of regional spending. The population of this study is budget realizationreport of revenue and expenditure regional in Rokan Hilir Regency from 2011-2016. This research method uses total sampling, which is a sample that representsthe population because it is considered small or less than one hundred. Themethod of analysis was carried out using descriptive analysis based on casestudies. The results of the tests that have been carried out. The total averageregional independence ratio is 4,52%, which is included in the very low category.The total average efficiency ratio of regional income is 102.63% which isincluded in the inefficient category. The total average ratio of the effectiveness ofregional income is 81.95%, which is included in the category quite effective. Thetotal average regional expenditure efficiency ratio is 66,63% which is included inthe efficient category. The total average ratio of regional expenditureeffectiveness is 71.46%, which is included in the category of ineffective. The totalaverage economic ratio of regional expenditure is 71.46%, which is included inthe economic category.Keyword : regional independence ratios, regional income efficiency ratios,regional income effectiveness ratios, regional expenditure efficiencyratios and economic ratios of regional spending and financialperformance.